2005
DOI: 10.1590/s1415-47572005000500028
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of the mutagenic potential and phytochemical characterization of oleoresin from Copaifera duckei Dwyer

Abstract: We characterized the chemical constituents of Copaifera duckei oleoresin and used dermal application to Wistar rats to evaluated its possible mutagenic and cytotoxic activities on peripheral blood reticulocytes and bone marrow cells. Chemical characterization of the oleoresin revealed the presence of sesquiterpene hydrocarbons, an unidentified neutral diterpene and diterpene acids. To evaluate mutagenicity evaluation the rats were treated with 10, 25 and 50% of the LD 50 dose of the oleoresin for three consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
8
1
3
Order By: Relevance
“…Furan itself is known to be oxidized by cytochrome P450 to yield chemically reactive and cytotoxic α , β -unsaturated dialdehydes [45]. However, oral administration to Wistar rats of Copaifera duckei oil (containing 59.3% of furanoid hardwickiic acid), for three consecutive days, only showed significant cytotoxicity at doses between 25% and 50% of the previously assessed LD 50 dose [46]. Interestingly, C2 and C3 oils presented 34.7% of furanoid derivatives, which were absent in C1 e C4.…”
Section: Discussionmentioning
confidence: 99%
“…Furan itself is known to be oxidized by cytochrome P450 to yield chemically reactive and cytotoxic α , β -unsaturated dialdehydes [45]. However, oral administration to Wistar rats of Copaifera duckei oil (containing 59.3% of furanoid hardwickiic acid), for three consecutive days, only showed significant cytotoxicity at doses between 25% and 50% of the previously assessed LD 50 dose [46]. Interestingly, C2 and C3 oils presented 34.7% of furanoid derivatives, which were absent in C1 e C4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research about the genotoxicity of different species of Copaiba reported the lack of genotoxicity of the genus Copaifera on the Micronu cleus test. Maistro et al 35 and dos Santos et al 36 had shown that oleoresin of C. dukei and C. martii, respectively, were no genotoxic at the highest doses evaluated in mice. A recent study of oleoresins and leaves extract of 6 Copaifera species (that include C. paupera) showed no genotoxic effect in vivo and in vitro Micronucleus test.…”
Section: Antigenotoxic Potential (Micronucleus Test and Alkaline Comementioning
confidence: 96%
“…Assim, diversos autores desenvolveram diferentes experimentos que corroboraram as atividades farmacológicas do oleorresina, tais como, ação anti-inflamatória, cicatrizante, antimicrobiana, antifúngica, leishmanicida e contra T. cruzi. Além disso, o óleo também foi avaliado para o tratamento de úlcera, doenças de pele e câncer (PAIVA et al, 1998(PAIVA et al, , 2002TINCUSI et al, 2002;LIMA et al, 2003;CASTRO-E-SILVA et al, 2004;CARVALHO et al, 2004MAISTRO et al, 2005;VEIGA JUNIOR, 2006OLIVEIRA et al, 2007;VIEIRA et al, 2008;SANTOS et al, 2008a;SANTOS et al, 2008b;GOMES et al, 2008;PIERI et al, 2009;DEUS et al, 2009;MENDONÇA, ONOFRE, 2009;IZUMI et al, 2013) Certamente, a atividade antimicrobiana é uma das propriedades mais avaliadas (LEANDRO et al, 2011 É importante ressaltar, que a capacidade das plantas em sintetizar substâncias tóxicas que naturalmente agem na defesa contra diferentes patógenos, pode ainda ser citotóxica quando administrados no organismo humano (IZUMI et al, 2012). Assim, embora a atividade farmacológica do oleorresina e dos diversos terpenos seja expressiva, uma atividade hemolítica e citotóxica moderada tem sido relatada (COSTA-LOTUFO et al, 2002;IZUMI et al, 2012, SARTORELLI et al, 2010.…”
Section: Oleorresina De Copaíba E Constituintes Com Atividade Farmacounclassified
“…A DL50 oral é definida como a quantidade de uma substância necessária para matar 50 % de uma população de animais submetidos a uma única administração via oral dentro de um curto período de tempo. É importante citar ainda, que Maistro et al (2005) Os produtos naturais e os derivados naturais ou sintéticos representam a maioria dos medicamentos em uso clínico no mundo (NEWMAN et al, 2003;GURIB-FAKIM, 2006 Apêndice I -Espectro de HSQC do 4,11,11-trimetil-8-metilenobiciclo[7.2.0]undec-3-en-5-ol (400/100 MHz, CDCl3). …”
Section: Reação De D2 E D3 Com Iodo (I)unclassified